2020
DOI: 10.3389/fpubh.2020.579705
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Ion Therapy Inhibits Esophageal Squamous Cell Carcinoma Metastasis by Upregulating STAT3 Through the JAK2/STAT3 Signaling Pathway

Abstract: Radiation therapy is an important component of the comprehensive treatment of esophageal cancer. However, conventional radiation resistance is one of the main reasons for treatment failure. The superiority of heavy ion radiation in physics and biology has been increasingly highlighted in radiation therapy research. The Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) pathway plays an important role in the occurrence, development and metastasis of esophageal squamous cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…We observed that the colony formation rate of A549 cells irradiated with carbon ion rays was significantly lower, and the colony formation rate and survival fraction of A549 cells were significantly lower after irradiation at each dose (1, 2, and 4 Gy) compared with 0 Gy, especially this change was most pronounced at 4 Gy. Carbon ions could inhibit the proliferation of A549 cells, and the activity of A549 cells was the lowest at 24 h after irradiation, as we previously observed in esophageal cancer ( 21 ). Secondly, we studied the effect of carbon ion irradiation on the metastasis of A549 cells, and analyzed the migration and invasion of A549 cells after carbon ion irradiation.…”
Section: Discussionsupporting
confidence: 78%
“…We observed that the colony formation rate of A549 cells irradiated with carbon ion rays was significantly lower, and the colony formation rate and survival fraction of A549 cells were significantly lower after irradiation at each dose (1, 2, and 4 Gy) compared with 0 Gy, especially this change was most pronounced at 4 Gy. Carbon ions could inhibit the proliferation of A549 cells, and the activity of A549 cells was the lowest at 24 h after irradiation, as we previously observed in esophageal cancer ( 21 ). Secondly, we studied the effect of carbon ion irradiation on the metastasis of A549 cells, and analyzed the migration and invasion of A549 cells after carbon ion irradiation.…”
Section: Discussionsupporting
confidence: 78%
“…Another study found that miR-21 could promote STAT3 by binding to the STAT3 promoter. All those studies suggest that miR-21 is closely related to the activation of the JAK2/STAT3 signaling pathway (23). In our study, the levels of JAK2 and STAT3 mRNA in the DUSP1 OVG of CC cells were significantly reduced compared with those in the C33a COG.…”
Section: Discussionsupporting
confidence: 50%
“…Our previous carbon ion irradiation studies of ESCC cells in different differentiation states found that a high dose of carbon ions prolongs G2/M cell cycle arrest, promotes apoptosis, and inhibits cell proliferation significantly. Carbon ion inhibiting sustained STAT3 activation via blocking of the JAK2/STAT3 signaling pathway, which leads to inhibition of migration and invasion in ESCC cells 11 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, carbon ion rays induced significant necrosis in the central region of the tumor, but X-ray induced only mild necrosis [10]. We have previously found that carbon ion radiation promotes apoptosis and inhibits cell proliferation in esophageal squamous carcinoma cells through cell experiments [11]. However, high LET radiation causes more complex protein modification changes through posttranslational and oxidative processes, making the specific targets and mechanisms of radiation-mediated biological phenotypes remain unclear.…”
Section: Introductionmentioning
confidence: 99%